Productivity accounting on an operating mine - Cockcroft, Darryl Clem (My University, 1996)
Industry in South Africa, and in particular the mining industry is faced with unprecedented challenges to remain profitable. [Abbreviated Abstract. Open document to view full version]
A project report submitted to the faculty of Engineering, University of the Witwatersrand, in partial fulfillment of the requirement for the degree of master of science in engineering
Keywords: Productivity accounting--South Africa; Mines and mineral resources--Economic aspects--South Africa; Labor productivity--South Africa; Mines and mineral resources--Labor productivity